2012
DOI: 10.1136/annrheumdis-2011-201024
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete response of inflammatory arthritis to TNFα blockade is associated with the Th17 pathway

Abstract: These findings, which need to be confirmed in a larger cohort, suggest that a Th17-targeted therapeutic approach may be useful for anti-TNFα non-responder patients or as an adjunct to anti-TNFα therapy, provided that safety concerns can be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 18 publications
8
123
0
6
Order By: Relevance
“…Th17 and Th1 cells paradoxically increase in RA patients following anti-TNF therapy, an observation first seen in the CIA model (Notley et al, 2008). Blockade of TNF results in an increase in the IL-12/IL-23 subunit p40 (IL-12 and IL-23 are important for Th1 and Th17 survival, respectively) and further studies have linked increased Th17 and Th1 cells with nonresponse to anti-TNF in RA patients (Alzabin et al, 2012;Chen et al, 2011).…”
mentioning
confidence: 99%
“…Th17 and Th1 cells paradoxically increase in RA patients following anti-TNF therapy, an observation first seen in the CIA model (Notley et al, 2008). Blockade of TNF results in an increase in the IL-12/IL-23 subunit p40 (IL-12 and IL-23 are important for Th1 and Th17 survival, respectively) and further studies have linked increased Th17 and Th1 cells with nonresponse to anti-TNF in RA patients (Alzabin et al, 2012;Chen et al, 2011).…”
mentioning
confidence: 99%
“…Building on earlier reported effects of TNF inhibition on the IL-17 pathway 17 , the authors have observed that increased levels of plasma n-3 FA were associated with decreased expression of IL-17, resulting in a consequent enhanced clinical response to TNF inhibition. It is interesting that the patients in this small trial were not described as consuming a diet high in n-3 and were not given supplements containing these FA.…”
Section: Rheumatologymentioning
confidence: 99%
“…As noted, the authors place their observation in the context of previously established inhibitory mechanisms of TNF itself on the production of IL-17 17 . Thus inhibition of TNF would be expected to enhance IL-17 production with the potential to abrogate the beneficial clinical effects of TNF inhibition.…”
Section: Rheumatologymentioning
confidence: 99%
“…Резистентность к ингибиторам ФНОα ассо-циируется с увеличением числа Th17-клеток в перифери-ческой крови, концентрации р40 (субъединица ИЛ12 и ИЛ23), а также тенденцией к более выраженной про-дукции ИЛ17 ex vivo периферическими мононуклеарны-ми клетками, выделенными из крови больных с РА. Кро-ме того, высокий базальный уровень Th17-клеток ассо-циируется с отсутствием положительной динамики инде-кса DAS28 на фоне терапии [89].…”
Section: таблицаunclassified
“…Не удивительно, что «двойная» блокада ИЛ17 и ФНОα с помощью соот-ветствующих антител к этим цитокинам более эффектив-но подавляет воспаление и деструкцию суставов при кол-лагеновом артрите у мышей, чем монотерапия каждым из них [170]. Имеются данные о том, что у некоторых боль-ных РА увеличение числа Th17-клеток и концентрации ИЛ17 в сыворотке крови ассоциируется с резистентно-стью к терапии ингибиторами ФНОα [88,89], а на фоне лечения этими препаратами наблюдается парадоксаль-ное нарастание числа Th17-клеток и синтеза р40 (субъ-единица ИЛ12 и ИЛ23) [89,171,172]. Создается впечат-ление, что ингибирование ФНОα не всегда контролирует и даже может способствовать активации Th17-типа им-мунного ответа [173].…”
Section: перспек тивыunclassified